Faulheit Verboten“ — Zeitkritik bei Hallgrfmur Petursson und Stefan Ólafsson - Kreutzer, Gert (Folia Scandinavica Posnaniensia, 2007)
This article discusses works by Icelandic baroque poets Hallgrimur Petursson (1614-1674) and Stefan Ólafsson (1619-1667) that are critical of contemporary issues, also taking into account their 17lh-century historical background. Both poets were pastors and found ample occasion for criticizing the moral, economic and political state of affairs in their country. In particular, the poems “Passiusalmar” and “Aldarhittur" by Hallgrimur Péursson, among others, as well as “Danskurinn”, “Um fyrri og |)essa old” and “Ómennskukvae5i” by Stefan Olafsson are presented and analyzed with respect to content and form.